The Relationship between Jobs and Social Cohesion : Some examples from Ethnography - Dudwick, Nora (World Bank, Washington, DC, 2013)
This paper uses selected case studies to illustrate some of the complex relationships that link employment and social cohesion. For example, despite harsh working conditions, retail garment manufacturing contributed to the transformation of gender relationship in Bangladesh by giving women the opportunity to acquire skills, control over resources, and greater independence. Conversely, the downsizing of industries in the US, Argentina, Bulgaria, and Guyana not only hurt households financially; it undermined their sense of dignity, self-worth, and trust in institutions, and severely weakened social ties within their communities. Chronic unemployment and underemployment does more than erode social cohesion—in the Arab Spring, it helped catalyze a broad-based social movement that overturned regimes; in the UK, a pervasive sense of exclusion from economic life provoked a disorganized and violent reaction. Since the relationship between jobs and social cohesion is mediated by institutions and policies, policy makers should be more proactive in considering policies to help cushion the impacts of changing labor markets and/or joblessness in the interests of maintain social stability and cohesion.